Ageing and its Implications for Elderly Web Experience - Hisham, Syariffanor; Edwards, Alistair D. N. (Idea Group Publishing, 2007)
This chapter discusses ageing related issues and their implications to the Web experience of elderly users. Particular emphasis is placed on ageing in a developing region highlighting some cases from Malaysia. The first section consists of a brief review regarding ageing functional abilities and their implications for Web interaction. Examples are given based on studies by other researchers in this area, covering major age-related impairments, namely visual and mental impairment. The potential benefits of the Internet and the elderly user as an ideal partner is examined. The second section presents more examples of the Internet as a platform for elderly people to pursue self-fulfillment. This can be achieved through the available facilities, including communication, services, personal enjoyment and lifelong education which facilitate an independent life and valued membership of society. The third section investigates some of the barriers that inhibit elderly users in utilising Web features. These include issues regarding interface design, assistive devices and software aids for elderly users. A summary of the ICT penetration among elderly users in Malaysia is included after the three main sections. Finally, the chapter is concluded with some ideas concerning the cultural and demographic differences in determining new trends, directions and opportunities in advanced Web design specifically for elderly users.